Job insecurity and work–family conflict: A moderated mediation model of perceived organizational justice, emotional exhaustion and work withdrawal. Issue 5 (9th March 2020) - Nauman, Shazia; Zheng, Connie; Naseer, Saima
Abstract : Purpose: Drawing on conservation of resources theory, this study aims to investigate the processes underlying the linkages between job insecurity (JI) and work–family conflict (WFC) from a stress perspective, focusing on the mediating role of subordinates' work withdrawal (WW) and emotional exhaustion (EE). Specifically, the authors tested two distinct mediating mechanisms, namely, WW and EE that have received less attention in testing the JI and WFC linkage. The authors also tested the variable of perceived organizational justice (POJ) to moderate these relationships. Design/methodology/approach: Survey data collected at Time 1 and Time 2 included 206 professionals from different occupational sectors. The authors study independent variable (i.e. JI), moderator (POJ) and mediator (WW) were measured at Time-1, whereas the other mediator (EE) and outcome (WFC) were tapped by the same respondent at Time-2 with a time interval of one month between them. Findings: The findings suggest that subordinates' EE and WW mediate the relationship between JI and WFC. Further, the authors found that EE is a relatively more effective mechanism than WW in explaining how and why JI translates into WFC. The results of the moderated mediation analysis revealed that the indirect effect of JI on WFC is strengthened when POJ is low. Practical implications: JI has adverse consequences on the employees' well-being and a cost to the organization in terms of WW. HR and top management should anticipate the negative influence of WW and EE and should focus on nurturing positive work–family climates to help reduce WFCs. Managers should give employees opportunities for participation and foster a climate of fairness in the organization to mitigate the harmful consequences of JI. Originality/value: This study contributes to the employees' burnout, counter work behavior and the WFC literature. By introducing EE and WW as underlying mechanisms and identifying POJ as a work contextual variable to explain the JI – WFC relationship, the authors extend the nomological network of JI. The authors respond to the calls by prior researchers as little research has examined how perceived fairness (unfairness) can induce WFC.